2013
DOI: 10.1177/1077695813478180
|View full text |Cite
|
Sign up to set email alerts
|

The Mass Comm Type

Abstract: A study of news media and strategic communication majors ( n = 273) revealed differences in regard to personality indices and impetuses for selecting to pursue degrees. Showing overall agreement in the importance of openness, agreeableness, and conscientiousness, strategic communication students were significantly higher in their ratings of agreeableness. News media students were significantly higher in their ratings of openness. In addition, news media students stated a significantly higher rating of the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a study of U.S. journalism students, degree motivations differed for students farther along the degree program as they became more realistic and less idealistic about journalism's ability to foster social change or bring fame and fortune to practitioners (Carpenter et al, 2015). News media students in another study awarded significantly higher ratings for openness to experience and the importance of altruism, as compared to students in strategic communication (Crawford et al, 2013). Australian students emphasized a desire for a varied lifestyle and ability to practice creative skills among the top motivations, with public service in the middle; financial concerns and fame were deemphasized (Hanusch et al, 2016).…”
Section: Journalism Degree Motivationsmentioning
confidence: 99%
“…In a study of U.S. journalism students, degree motivations differed for students farther along the degree program as they became more realistic and less idealistic about journalism's ability to foster social change or bring fame and fortune to practitioners (Carpenter et al, 2015). News media students in another study awarded significantly higher ratings for openness to experience and the importance of altruism, as compared to students in strategic communication (Crawford et al, 2013). Australian students emphasized a desire for a varied lifestyle and ability to practice creative skills among the top motivations, with public service in the middle; financial concerns and fame were deemphasized (Hanusch et al, 2016).…”
Section: Journalism Degree Motivationsmentioning
confidence: 99%
“…The study also found differences between students and faculty in terms of their preferences for the teaching of skills versus the teaching of theoretical knowledge. It makes sense intuitively that mass communication students might form preferences for certain media platforms and associated skills based in part on the biases of their professors or even on personality traits (Crawford, Hubbard, & Filak, 2009; Netzley & Banning, 2011), and there is enough research into the implications of media convergence on journalism to support such an assumption (Ying & Thornburg, 2011). It is also logical, however, to suggest such biases and preferences might exist among strategic communication students as well, although few if any studies have looked specifically at this idea.…”
mentioning
confidence: 99%